Clonal Evolution Leading to Maintenance of Antibiotic Resistance Rates among Colonizing Pneumococci in the PCV7 Era in Portugal - Simões, Alexandra S. (American Society for Microbiology, 2011)

(untitled)
The introduction of the seven-valent pneumococcal conjugate vaccine (PCV7) in Portugal led to extensive serotype replacement among carriers of pneumococci, with a marked decrease of PCV7 types. Although antimicrobial resistance was traditionally associated with PCV7 types, no significant changes in the rates of nonsusceptibility to penicillin, resistance to macrolides, or multidrug resistance were observed. This study aimed to investigate the mechanisms leading to maintenance of antimicrobial resistance, despite marked serotype replacement. We compared, through molecular typing, 252 antibiotic-resistant pneumococci recovered from young carriers in 2006 and 2007 (era of high PCV7 uptake) with collections of isolates from 2002 and 2003 (n=374; low-PCV7-uptake era) and 1996 to 2001 (n=805; pre-PCV7 era). We observed that the group of clones that has accounted for antimicrobial resistance since 1996 is essentially the same as the one identified in the PCV7 era. The relative proportions of such clones have, however, evolved substantially overtime. Notably, widespread use of PCV7 led to an expansion of two Pneumococcal Molecular Epidemiology Network (PMEN) clones expressing non-PCV7 capsular variants of the original strains: Sweden(15A)ST63 (serotypes 15A and 19A) and Denmark(14)ST230 (serotypes 19A and 24F). These variants were already in circulation in the pre-PCV7 era, although they have now become increasingly abundant. Emergence of novel clones and de novo acquisition of resistance contributed little to the observed scenario. No evidence of capsular switch events occurring after PCV7 introduction was found. In the era of PCVs, antimicrobial resistance remains a problem among the carried pneumococci. Continuous surveillance is warranted to evaluate serotype and clonal shifts leading to maintenance of antimicrobial resistance.